2016
DOI: 10.1002/2016ja022775
|View full text |Cite
|
Sign up to set email alerts
|

Observation of chorus waves by the Van Allen Probes: Dependence on solar wind parameters and scale size

Abstract: Highly energetic electrons in the Earth's Van Allen radiation belts can cause serious damage to spacecraft electronic systems and affect the atmospheric composition if they precipitate into the upper atmosphere. Whistler mode chorus waves have attracted significant attention in recent decades for their crucial role in the acceleration and loss of energetic electrons that ultimately change the dynamics of the radiation belts. The distribution of these waves in the inner magnetosphere is commonly presented as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(87 citation statements)
references
References 98 publications
6
81
0
Order By: Relevance
“…The majority of the waves are observed within 5° of the magnetic equator in all regions except at low L near dawn. The MLT distribution of the occurrence of the highest‐amplitude waves is clearly different than the distribution of mean chorus wave amplitude and power, which is maximum from dawn to noon in for higher L (Cully et al, ), and across the entire midnight‐to‐noon span in for lower L (Aryan et al, ).…”
Section: Statistical Resultsmentioning
confidence: 98%
“…The majority of the waves are observed within 5° of the magnetic equator in all regions except at low L near dawn. The MLT distribution of the occurrence of the highest‐amplitude waves is clearly different than the distribution of mean chorus wave amplitude and power, which is maximum from dawn to noon in for higher L (Cully et al, ), and across the entire midnight‐to‐noon span in for lower L (Aryan et al, ).…”
Section: Statistical Resultsmentioning
confidence: 98%
“…Poynting flux and polarization measurements on board Polar [LeDocq et al, 1998] and the Cluster spacecraft confirmed that the chorus source is located close to the equator Santolik et al, 2003;Santolík and Gurnett, 2003;Agapitov et al, 2011aAgapitov et al, , 2013Artemyev et al, 2016] and also that the dimension of the chorus source region measured along the magnetic field line is 3000-5000 km [Santolík and Gurnett, 2003;Agapitov et al, 2013]. Chorus generation region scales in the Earth's outer radiation belt were estimated theoretically [Helliwell, 1967;Trakhtengerts, 1999;Omura et al, 2008] and experimentally [Santolík and Gurnett, 2003;Breneman et al, 2007;Agapitov et al, 2010Agapitov et al, , 2011bAryan et al, 2016] using data from coordinated Cluster observations. Santolik et al [2003Santolik et al [ , 2004 and Santolík and Gurnett [2003] determined the correlation lengths of chorus-type whistler waves based on multipoint Cluster WBD measurements near the chorus source region during the magnetic storm of 18 April 2002 (at L shell about 4).…”
Section: Introductionmentioning
confidence: 82%
“…Poynting flux and polarization measurements on board Polar [ LeDocq et al ., ] and the Cluster spacecraft confirmed that the chorus source is located close to the equator [ Parrot et al ., ; Santolik et al ., ; Santolík and Gurnett , ; Agapitov et al ., , ; Artemyev et al ., ] and also that the dimension of the chorus source region measured along the magnetic field line is 3000–5000 km [ Santolík and Gurnett , ; Agapitov et al ., ]. Chorus generation region scales in the Earth's outer radiation belt were estimated theoretically [ Helliwell , ; Trakhtengerts , ; Omura et al ., ] and experimentally [ Santolík and Gurnett , ; Breneman et al ., ; Agapitov et al ., , ; Aryan et al ., ] using data from coordinated Cluster observations. Santolik et al .…”
Section: Introductionmentioning
confidence: 99%
“…The spatial scale of the whistler mode waves (especially the transverse scale) is one of the important but not well‐understood characteristics of the waves. In the magnetosphere, multispacecraft observations of chorus waves (Agapitov et al, 2010; Agapitov et al, 2011; Agapitov et al, 2017; Agapitov et al, 2018; Aryan et al, 2016; Santolík et al, 2003; Santolík et al, 2004; Santolík & Gurnett, 2003; Shen et al, 2019; Turner et al, 2017) and indirect estimation from the comparison between spacecraft observations around the magnetic equator and ground observations of pulsating aurora at the magnetic footprint (Kawamura et al, 2019; Nishimura et al, 2010; Nishimura et al, 2011; Ozaki et al, 2018; Ozaki et al, 2019) indicate that the transverse spatial scale is from tens to several thousands of kilometers mapped to the magnetic equator (source). In the present study, the enhancements of whistler mode waves in the magnetosheath were seen over a wide region in troughs of B 0 , and all spacecraft simultaneously observed them probably because of the separation (~40 km), which was much smaller than the mirror mode structures.…”
Section: Discussionmentioning
confidence: 99%